Mind the gap: health disparities in families living with epilepsy are significant and linked to socioeconomic status. Issue 6 (21st January 2021) - Groover, Olivia; Morton, Matthew L.; Janocko, Nicholas J.; Teagarden, Diane L.; Villarreal, Hannah K.; Drane, Daniel L.; Karakis, Ioannis
Abstract: Aims . There is limited information on disparities of people with epilepsy (PWE) and, foremost, their caregivers. The objective of this study was to comprehensively compare between PWE and caregivers with low socioeconomic status (SES) and those with high SES for disparities in demographic and epilepsy characteristics, treatment and health care utilization, physical and psychosocial impact, and knowledge about epilepsy. Methods . PWE and caregivers completed surveys about the aforementioned outcomes during their epilepsy clinic visit or epilepsy monitoring unit admission. Associations were evaluated using SES as a binary independent variable and the patient and caregiver related outcomes as dependent variables. Results . Thirty‐eight patients with low SES and 88 patients with high SES were recruited. Patients with low SES were more commonly non‐white, uninsured, unemployed, of lower educational attainment and living in larger households. They were more likely to visit the emergency room for their seizures, were more frequently on polypharmacy and experienced more AED adverse effects. They exhibited higher depression and anxiety levels and worse quality of life. Twenty‐two caregivers with low SES and 66 caregivers of high SAS were recruited. Caregivers with low SES were more likely to be non‐white and single. They manifested poorer knowledge about epilepsy. Conclusion . There are notable inequalities in demographic, treatment‐related and health care utilization aspects of care of PWE, as well as in the psychosocial impact of their disease. Additional demographic and epilepsy knowledge‐related disparities are recognized in caregivers of PWE. Identification of those disparities is a critical step in the creation of appropriate interventions to eliminate them.